Parasitic leiomyomas: a systematic review. (August 2016) - Lete, Iñaki; González, Janire; Ugarte, Lorea; Barbadillo, Nagore; Lapuente, Oihane; Álvarez-Sala, Javier
Abstract: Background: Parasitic leiomyomas were first described as early as 1909 but are a rare condition. In recent years, due to the rise of laparoscopic surgery and power morcellation, several cases of parasitic leiomyomas associated with this surgical procedure have been reported. Methods: A literature search was performed using PubMed, Embase and Google Scholar with the following combination of keywords: leiomyoma OR uterine neoplasms OR uterine myomectomy OR laparoscopy OR hysterectomy OR peritoneal neoplasms AND parasitic. Papers describing parasitic leiomyomas were included. The results of these studies are summarized herein. Results: We retrieved abstracts of 756 papers. Of these, 591 were excluded for not fulfilling the inclusion criteria and 54 were removed as duplicates; after full-text assessment, 8 were rejected for presenting cases of malignancy and finally 103 were included in our systematic review. From these, we present information about 274 patients with parasitic leiomyomas. The mean age of women was 40 years (range 18–79 years); and 154 (56%) had no history of uterine surgery, the others (120, 44%) having had a previous myomectomy or hysterectomy. Of the total, 106 (39%) women had a history of power morcellation. The most frequent clinical symptom was abdominal pain (49%) and the most frequent presentation was disseminated peritoneal leiomyomatosis. Conclusions: While parasitic leiomyoma was first described a century ago, the recent introduction of laparoscopic power morcellation has increased the number of reported cases.